2017
DOI: 10.22146/tradmedj.27926
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Papaya Seed Extract (Carica papaya Linn.) on Glucose Transporter 4 (GLUT 4) Expression of Skeletal Muscle Tissue in Diabetic Mice Induced by High Fructose Diet

Abstract: Ethnobotany surveys show that papaya seeds are widely used as herbs for the management of some diseases such as abdominal discomfort, pain, malaria, diabetes, obesity, and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 2 publications
(2 reference statements)
1
7
0
Order By: Relevance
“…Papaya seed extract is rich in flavonoids and phenolic acid having important role as antioxidants and anti-hyperglycemia. Previous studies have shown that papaya seed extract can increase GLUT4 expression in hyperglycemic mice so that it can increase glucose uptake into insulin sensitive tissue [9]. The results of this study indicated that papaya extract at a dose of 200 and 300 mg/kg BW were able to improve the atrophy of skeletal muscle cells that occurs in hyperglycemia conditions.…”
Section: Resultsmentioning
confidence: 50%
See 2 more Smart Citations
“…Papaya seed extract is rich in flavonoids and phenolic acid having important role as antioxidants and anti-hyperglycemia. Previous studies have shown that papaya seed extract can increase GLUT4 expression in hyperglycemic mice so that it can increase glucose uptake into insulin sensitive tissue [9]. The results of this study indicated that papaya extract at a dose of 200 and 300 mg/kg BW were able to improve the atrophy of skeletal muscle cells that occurs in hyperglycemia conditions.…”
Section: Resultsmentioning
confidence: 50%
“…Prolonged fructose induction can cause desensitization and downregulation of insulin receptors so that it can interfere Tabel 1. Body weight and fasting blood glucose level in the diabetic and the treatment rat group at the initial and final of study with intracellular GLUT4 translocation into the plasma membrane of skeletal muscle cells which subsequently causes a decrease in glucose uptake by insulin-sensitive tissues such as skeletal muscles, causing hyperglycemia conditions [9,14]. In this study, the results showed that in hyper-glycemic conditions, the area of skeletal muscle cells in rat gastrocnemius was smaller (Figure 3b) than those of normal rat (Figure 3a).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rats were induced by administering 20% fructose solution orally at a dose of 1.86 grams/kg body weight since day 1 until day 60 days which is expected to induce insulin resistance (Wulansari 2017). Celery extract is also given orally on day 1 until day 60 in adjusted dose of treatment.…”
Section: Methodsmentioning
confidence: 99%
“…The tissue pieces then colored by soaking in lithium carbonate and rinsing with running water. because it is able to recognize several epitopes and cross reactivity can occur (Konrad et al, 2002;Wulansari, 2017). pieces are placed in 1% alcoholic acid for a few seconds before rinsing again with running water and soaked in eosin for 5 minutes.…”
Section: Calculation Of Homa-irmentioning
confidence: 99%